Hubungan Tingkat Pengetahuan dan Sikap dengan Kesiapsiagaan Bencana Banjir pada Mahasiswa Kesehatan di DKI Jakarta - Yari, Yarwin; Ramba, Hardin La; Yesayas, Fendy (Jurnal Kesehatan Holistic, 2021)
Floods are the world's leading natural disaster. Nursing students as prospective nursing staff are required to know the actions in disaster preparedness. As the spearhead in health services, nurses have an important role in every disaster event in the world. This research was carried out by DKI Jakara. This type of research is quantitative with a cross-sectional design. The sample in this study were DIII Nursing students in DKI Jakarta, 98 respondents. The results showed that 93.9% of respondents had sufficient knowledge, 90.8% of respondents were in the positive attitude category, and 86.7% of respondents were in the ready category. Based on the results of the multivariate statistical analysis of knowledge with preparedness, it was obtained a value (p value 0.006 < 0.05), attitude with preparedness obtained a value (p value 0.004 < 0.05). The conclusion is that there is a significant relationship between the level of knowledge and attitudes with disaster preparedness in students. As prospective nurses, it is hoped that students will continue to improve disaster knowledge, especially about floods through training related to nurse skills, and add to the list of reading references and always be able to apply a positive attitude and always be a motivator for the community in disaster preparedness effort.